Tia Tape Measure - F Klein, Adria; Rowland, Andrew (Mankato, Minn Stone Arch Books, 2012)
Tia Tape Measure helps measure shelves so the new library books can be put away
A gift from book Africa
Science
1 2 13 15
Keywords: Libraries -- Juvenile fiction; Measurement -- Juvenile fiction; Tools -- Juvenile fiction